Schiffsfinanzierung im Wandel: Finanzintermediäre und maritime Wirtschaft am Finanzplatz Hamburg - Harald Wixforth (IBF - Institut für Bank- und Finanzgeschichte, 2017)
– The relationship of companies in the maritime economy to banks has been neglected by researchers. While this is surprising, specific financing techniques in ship financing can be found. In addition, the topic has a high degree of currency: the relationship of shipping companies and shipyards to private and public financial intermediaries has come under massive criticism, especially since the last financial and banking crisis. A number of banks are accused of virtually initiating the new construction of vessels through reckless lending, which thus created a large volume of excess tonnage. In addition, the loans were allegedly often insufficiently collateralized so that a major portion had to be written off, which weighed down the banks' balance sheets. In political debate as well the topic was a "permanent issue" in the face of impending massive charges to the government. If one looks at the spectacular bankruptcies that have recently rocked both the maritime economy and the banking sector, the suspicion naturally arises that the ship financing business could be especially susceptible to a crisis. On the other hand, previous research findings show that a number of financial intermediaries, especially those located in the North and Baltic Sea areas important to shipbuilding, classified shipbuilding financing as rich in prospects and a lucrative business segment. Recourse to the past can clarify whether and the extent to which ship financing contained certain risks. This article intends to clarify this question for Hamburg - without question one of the most important German locations for both the maritime sector and the lending business.
Keywords: G21; N23; N24; N93; N94; 330